Eksperimental Penambahan Graphene Sebagai Zat Aditif Pada Campuran Asphalt Concrete Binder Course (AC-BC) - Ali Novia; Muhammad Shalahuddin; Yosi Alwinda; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The type of pavement commonly used in Indonesia is flexible pavement that uses asphalt as its binding material. It is very important to maintain the characteristic of asphalt that functions as the aggregate adhesive in a mixture of asphalt concrete (laston). One way of maintaining or improving the characteristics of the laston is by using graphene as an additive. This study was aimed to examine and analyze the effect of adding graphene as an additive and to find out the most effective level of graphene addition in the asphalt mixture to the Marshall characteristics of the AC–BC laston mixture. This study combined the addition of graphene as an additive of 3.5%, 4%, and 4.5% of the weight of asphalt. The test results showed that the stability value of Marshall characteristics at optimum bitumen content conditions is increased. The highest stability value is found in the addition of 4.5% of graphene which is 1500 kg. The most effective level of graphene addition in the asphalt mixture against Marshall characteristics is by adding 4.5% graphene. The addition of 4.5% of graphene has the highest stability value with a difference of 200 kg or 14.81%, while the value of flow is 4,5 mm, VIM is 3.7%, VFA is 76%, VMA is 14,8%, and MQ is 350 kg/mm, all these values fulfill Bina Marga specifications 2010 revision 3, except the flow values.Keywords: Graphene, Marshall characteristics, AC–BC, Laston